Supervisor experience and cybersecurity response in aviation organizations using a two-wave exploratory design - Filiz Mizrak; Kagan Cenk Mizrak; Umut Elbir (PLoS ONE, 2025)
As cybersecurity threats continue to intensify across safety-critical industries, the aviation sector faces unique challenges due to its high digital dependency and human-centered operational environments. This study investigates how aviation supervisors in Türkiye perceive and respond to cybersecurity incidents involving employees, focusing on the psychological dimensions of leadership under pressure. Using a two-wave mixed-method design, data were collected from 300 supervisors through structured surveys and open-ended reflections on recent cybersecurity-related incidents. Thematic analysis identified common incident types such as phishing, password negligence, and unauthorized device use, along with eight distinct supervisory response strategies. Supervisors rated their actions on stressfulness and effectiveness, and K-means cluster analysis revealed three psychological response profiles. Multinomial logistic regression showed that psychological distress and time pressure were significant predictors of unfavorable experiences, while organizational cybersecurity support reduced the likelihood of high stress and low perceived effectiveness. These findings contribute to psychosocial risk and critical incident theory by highlighting cybersecurity incidents as emotionally significant events and underscore the need for supervisor training that integrates emotional resilience and cyber preparedness.